Turkestan educators and Ismail Gasprinsky (Based on the materials of the Bakhchisarai Museum-Reserve and the newspaper “Terdzhiman”) - Selvina Seitmemetova (Крымское историческое обозрение, 2021)
Based on the materials of the newspaper “Terzhiman” and books with gift inscriptions stored in the funds of the Bakhchisarai historical, cultural and archaeological museum-preserve, the closest circle of Turkestan acquaintances, like-minded people and associates of the famous all-Turkic educator, editor, and publisher Ismail Bey Gasprinsky (1851–1914) is considered. The article reveals the role of the educator in the formation of the national periodical press, new-fashioned educational literature and the dissemination of the Jadid education system in the territory of Turkestan. Through the editorial notes of the newspaper “Terzhiman”, books and periodicals lost from the personal collection of I. Gasprinsky were identified. His personal and creative contacts with prominent Turkestan teachers, publishers and public figures are considered, such as: M. Behbudi, K. Khalidi, A. Shakuri, A. Avloni, M. Kary, etc.